Ellery Queen : MASTERS OF MYSTERY - Queen, Ellery, editor 641257; Sullivan, Eleanor,, editor 641395 (New York : Galahad Books, 1993)
NO CRIME SOLVER COLLECTION can be complete without this suspenseful anthology. Originally published in ELLERY QUEEN'S MYSTERY MAGAZINE, the tales in this volume represent many well known names in detective and suspense fiction, including P.D. James, Victor Canning, Jack Ritchie, Patricia Highsmith, Julian Symons, Lawrence Block, and of course, Ellery Queen.